2012
DOI: 10.1210/en.2011-1365
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Regeneration: Characterization of Clear Cells After Partial Thyroidectomy

Abstract: Although having the capacity to grow in response to a stimulus that perturbs the pituitary-thyroid axis, the thyroid gland is considered not a regenerative organ. In this study, partial thyroidectomy (PTx) was used to produce a condition for thyroid regeneration. In the intact thyroid gland, the central areas of both lobes served as the proliferative centers where microfollicles, and bromodeoxyuridine (BrdU)-positive and/or C cells, were localized. Two weeks after PTx, the number of BrdU-positive cells and cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
38
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(40 citation statements)
references
References 48 publications
2
38
0
Order By: Relevance
“…Possibly, no full restoration is needed to attain satisfactory hormone functions, or the mature organ, in contrast to the embryonic tissue, is not competent anymore for full restoration, as also found in other organs (see eg, [32][33][34]). In analogy, also other mature organs (e.g., thyroid gland, heart) only rarely regenerate to a full extent [8,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Possibly, no full restoration is needed to attain satisfactory hormone functions, or the mature organ, in contrast to the embryonic tissue, is not competent anymore for full restoration, as also found in other organs (see eg, [32][33][34]). In analogy, also other mature organs (e.g., thyroid gland, heart) only rarely regenerate to a full extent [8,35,36].…”
Section: Discussionmentioning
confidence: 99%
“…For the latter, it was previously demonstrated that partial thyroidectomy can be used as a model for thyroid regeneration (15). When SPTL cells were orthotopically injected into the thyroid, many GFP-positive cells were found outside as well as inside the thyroid (Supplementary Fig.…”
Section: Presence Of Sptl Cells In Part Of the Follicles In Vivomentioning
confidence: 95%
“…Thyroid SP cells highly express genes involved in cancer and/or cancer invasion/ metastasis, as determined by microarray analysis, compared with non-SP cells, suggesting that thyroid SP cells may contain cancer stem cells of the thyroid (14). Further, partial thyroidectomy was established as a model for studying thyroid regeneration (15). In the partial thyroidectomized thyroid, many clear cells due to scantiness of the cytoplasm, indicative of immature cells, were observed that have characteristics of either C cells or follicular cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…52 They evolve into functional follicles, which express TPO after 120 days, indicating that they consist of newly formed follicular cells, but do not originate from differentiated thyrocytes. 51,52 Considering the SCN as a source for both follicular and C cells, the presence of three cell types has been hypothesised: (i) progenitors of follicular cells, arisen from the base of the foregut (endodermal origin); (ii) progenitors of C cells, which originate from ultimobranchial bodies (neural crest origin); and (iii) and the follicular and C bipotential progenitor cells. 8 In 1992, Dumont et al 17 first hypothesised the existence of ASCs within the mature thyroid gland.…”
Section: Normal Thyroid Stem Cellsmentioning
confidence: 99%